Design and Building Mikrotik Based Billing System and Chatbot as Media Transaction Online - Wikantyasa, I Made Adhiarta; Suarjaya, I Made Agus Dwi; Raharja, I Made Sunia (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 9, No. 2, August 2021DO - 10.24843/JIM.2021.v09.i02.p07, 2021)
Providing services to rt / rw net users if done manually will consume a lot of time. Currently this service still used conventional methods even though there are applications that can help but still not efficient in providing the needs of the users such as transactions still using paper based vouchers, which will make it difficult for providers to provide time to handle user transactions. Besides that, there are also a problem where potential users of the service find a hard time to contact the provider because lack of knowledge of some of the provider to edit the mikrotik page to inform about their service and themselves to the user. With the problems mentioned, an application is needed that can provide much easier solution namely, "Design and Building Mikrotik Based Billing System and Chabot as Media Transaction Online". By making this application, it can provide much better solution for user such as getting information and interacting with the admin by using Chabot as media and online transaction to make it easier for users to update their packets and admin to process user transaction.